2020
DOI: 10.1002/ejic.202000048
|View full text |Cite
|
Sign up to set email alerts
|

Facile Solvothermal Synthesis of Black Phosphorus Nanosheets from Red Phosphorus for Efficient Photocatalytic Hydrogen Evolution

Abstract: In this work, we report a facial one‐step solvothermal synthesis of BP nanosheets from red phosphorus based on common laboratory conditions at low temperature. This bottom‐up approach for the direct preparation of BP nanosheets can be up to 2.1 g for one batch and the efficiency of the phase transition is up to 100 %. The as‐prepared BP nanosheets show highly efficient photocatalytic performance. Its efficiency of photocatalytic hydrogen evolution from water is 40.6 times higher than that of red phosphorus pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 49 publications
1
23
0
Order By: Relevance
“…The lateral size is between 0.8 and 2.0 µm, and the thickness is of about 4.7 nm with approximately 9 layers' flakes [55] Hydrothermal method…”
Section: Plus-laser Deposition Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lateral size is between 0.8 and 2.0 µm, and the thickness is of about 4.7 nm with approximately 9 layers' flakes [55] Hydrothermal method…”
Section: Plus-laser Deposition Methodsmentioning
confidence: 99%
“…Furthermore, a variety of methods to synthesize BPNSs have also been developed to meet certain application requirements. In addition, many other preparation methods are also reported or used for the synthesis of BPNSs, such as laser exfoliation, gas-phase growth strategy, plus-laser deposition, and the solvothermal method [ 54 , 55 , 69 , 70 ].…”
Section: Synthesis Of Black Phosphorus Nanomaterialsmentioning
confidence: 99%
“…[765] Hydro/solvothermal processes can also be used to produce 2D materials other than graphene and TMDCs. [281,766,767] Wang et al synthesized hexagonal Sb 2 Te 3 nanoplates with lateral dimensions of several microns by using hexadecyltrimethylammonium bromide (CTAB) as a structural directing agent during the solvothermal synthesis. [768] Shi et al later reported on the hydrothermal synthesis of single-crystalline, impurity-free Sb 2 Te 3 nanoplates without a structure-directing agent.…”
Section: Hydro/solvothermal Synthesismentioning
confidence: 99%
“…Based on these conditions, we can see that the hydro(solvo)thermal growth of 2D layered materials is usually performed at low relativetly temperature. Precursor: Ammonium molybdate tetrahydrate + absolute ethanol 180 ºC for 20 h. [427] Ethylenediamine +red phosphorus 165 ºC for 24 h [428] Bi(NO3)3.5H2O + acetic acid + KBr +deionized water 120ºC for 24h [429] BiOBr + ethanol + Co(OAc)2.4H2O + thiourea 180 ºC for 12h…”
Section: One-dimensional (1d) Materialsmentioning
confidence: 99%